Diseño de un juguete para ejercitar el desarrollo de la motricidad fina en niños de 3 a 5 años de edad - Ramírez Bastidas, Diego Fernando (Universidad Antonio Nariño, 2021)
The purpose of this project is to contribute to the development of children's society through a product that helps to exercise fine motor skills and that helps them generate new skills that allow them to grow day by day.